Perubahan Sosial Pada Komunitas Suku Bajo Di Pesisir Teluk Tomini - Muhammad Obie (IAIN Ponorogo, 2016)
Abstract: Society and culture of human being always change as an ever –present phenomena in the world. A distinction is sometimes made then between processes of change within the social structure, which serve in part to maintain the structure, and, even the processes itself can be slow or fast through evolusion and revolusion. One of the factors that quicken the social change process is the government interventions. This study aims at analyzing the social change on the Bajo Tribe community as the impact of various government programs at Tomini bay coastal. This research used strategy of historical sociology. The kinds of data collected were primer and secondary data that were analyzed by using qualitative approac. The result showed that various government programs at Tomini bay, such as designating conservation area, granting concession license to private sectors through forest concession right (FCR)), indefeasible right of use (IRU), and fishing industry at the bay had caused the loss of access of the Bajo tribe community to coastal and marine resources area. Various interventions of government programs had implication on resettlement of the Bajo tribe community, causing the Bajo tribe divided into sea Bajo and land Bajo. The loss of access of the Bajo tribe to coastal and marine resources caused traditional institution weaken which made its philosophy of living in harmony with nature, and conservation ethics fade away, its local wisdom, and self identity lose, and its social capital destructed. الملخص: كان المجتمع وحضارته متغيّرين في أيّ كان المجتمع وهذه الحضارة. ويكون الفرق في كون هذا التغيّر. قد تكون عملية التغيّر متمهّلة أو سريعة وقد تكون عن طريق التطوّر والثّورة. وأحد العناصر المسرعة في عملية هذا التغيّر هو تدخّل الحكومة. حاولت هذه الدراسة تحليل التغيّر الاجتماعي في قبيلة